Effects of cervical sympathectomy on vasospasm induced by meningeal haemorrhage in rabbits - Faleiros, Antonio Tadeu de Souza [UNESP]; Maffei, Francisco Humberto de Abreu [UNESP]; Resende, Luiz Antonio de Lima [UNESP] (Associação Arquivos de Neuro- Psiquiatria, 2006)
This study investigates the role of cervical sympathectomy in the prevention of acute vasospasm induced by meningeal haemorrhage in rabbits. Sixteen adult English Norfolk rabbits were divided into 2 experimental groups: bilateral cervical sympathectomy of the superior sympathetic ganglion (SSSG, n=8), and bilateral SSSG and sympathectomy of the inferior sympathetic ganglion (SISG, n=8). Other 24 animals were used as controls. Basilar artery diameter was evaluated by angiography. SSSG protected the animals against developing cerebral vasospasm; SSSG associated with SISG did not increase this effect.
Keywords: subarachnoid haemorrhage; vasospasm; cervical sympathectomy